Neurocysticercosis in non-endemic regions: The experience of Qatar - Naim Haddad; Naim Haddad; Yanal Shaheen; Mohammed Abunaib; Gayane Melikyan; Gayane Melikyan; Ahmed El Sotouhy; Farah Wahbeh; Areej Nauman; Fatima Al-Maadid; Mohamed Soliman; Boulenouar Mesraoua; et al. (Frontiers in Neurology, 2023)
ObjectiveTo describe the occurrence and features of Neurocystircercosis (NCC) in Qatar.BackgroundQatar has a mixed population of natives and expats. NCC is not endemic to the region, but clinical practice suggests its occurrence in large numbers.Design/ methodsA database was created to summarize information retrospectively collected on patients with NCC seen through the national health system (HMC) between 2013 and 2018. We identified demographic and disease related variables (clinical manifestations, investigative findings, treatment and outcome) for all patients.ResultsOut of 420 identified NCC patients, 393 (93.6%) were men, and 98.3% were immigrants from NCC endemic countries such as Nepal (63.8%) and India (29.5%). Eighty percent of patients presented with seizures, with the majority (69%) experiencing generalized tonic–clonic seizures. Five percent presented with status epilepticus. Headaches, the second most common complaint, were reported in 18% of subjects. On imaging, 50% had a single lesion while 63% included pathology at the calcified stage. The lesions were parenchymal in 99.5% of cases, predominantly in the frontal lobe (59%). Thirteen percent were diagnosed incidentally on imaging, mainly in the form of isolated calcified non enhancing lesions. Albendazole was received by 55% of patients, and phenytoin was the most prescribed anti-seizure drug (57%). When long term follow up was available, 70% of the patients presenting with seizures were completely seizure free.ConclusionNCC is prevalent in Qatar, mainly within the large Southeast Asian immigrant population. NCC is currently a significant contributor to the epilepsy burden in Qatar, often with a good outcome regarding seizure control. NCC with intraparenchymal single lesion shares a large proportion of our cohort.